2023
DOI: 10.3390/ijms242317096
|View full text |Cite
|
Sign up to set email alerts
|

Human Chondrocytes, Metabolism of Articular Cartilage, and Strategies for Application to Tissue Engineering

Darina Bačenková,
Marianna Trebuňová,
Jana Demeterová
et al.

Abstract: Hyaline cartilage, which is characterized by the absence of vascularization and innervation, has minimal self-repair potential in case of damage and defect formation in the chondral layer. Chondrocytes are specialized cells that ensure the synthesis of extracellular matrix components, namely type II collagen and aggregen. On their surface, they express integrins CD44, α1β1, α3β1, α5β1, α10β1, αVβ1, αVβ3, and αVβ5, which are also collagen-binding components of the extracellular matrix. This article aims to cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 171 publications
0
3
0
Order By: Relevance
“…Instead, SC-200, supplemented with a chondrogenic medium, partially maintained their rounded morphology. Previous research has demonstrated that insufficient cell density can result in suboptimal synthesis of extracellular matrix (ECM) and the loss of the functional phenotype of chondrocytes [60,61]. In contrast, high-density cultures preserve the spherical shape of chondrocytes, although excessive density may impede nutrient exchange and reduce ECM production [60].…”
Section: Discussionmentioning
confidence: 99%
“…Instead, SC-200, supplemented with a chondrogenic medium, partially maintained their rounded morphology. Previous research has demonstrated that insufficient cell density can result in suboptimal synthesis of extracellular matrix (ECM) and the loss of the functional phenotype of chondrocytes [60,61]. In contrast, high-density cultures preserve the spherical shape of chondrocytes, although excessive density may impede nutrient exchange and reduce ECM production [60].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the increase in the prevalence of this disease may cause a significant burden on the worldwide healthcare system 5 . Articular cartilage is a hyaline cartilage consisting mainly of chondrocytes and a dense extracellular matrix (ECM) 6 . ECM predominantly comprises type II collagen, proteoglycans, and other minor components 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Articular cartilage is a hyaline cartilage consisting mainly of chondrocytes and a dense extracellular matrix (ECM) 6 . ECM predominantly comprises type II collagen, proteoglycans, and other minor components 6 . In addition, chondrocytes play a crucial role in maintaining cartilage homeostasis through proliferation and secretion of their matrix and matrix-degrading enzymes 7 .…”
Section: Introductionmentioning
confidence: 99%